Proposed Strategy to Increase Brand Awareness in the Digital Market through Influencer and Content Marketing for SHAKTI Spice Product - Abirackshaan Wirajaya; Novika Candra Astuti (Journal of Social Research, 2025)
The low brand awareness of SHAKTI, a chili powder product owned by PT Sathrusi Komoditi Indonesia, presents a major challenge for entering Indonesia's competitive digital market, despite offering high-quality, halal-certified products, SHAKTI’s digital marketing efforts remain underdeveloped, this study investigates how influencer marketing and content marketing impact the improvement of brand awareness, a mixed-method approach was adopted, with quantitative data collected from 130 potential consumers via structured questionnaires, and qualitative data obtained through in-depth interviews with three internal stakeholders, multiple regression analysis revealed that both influencer marketing (? = 0.524) and content marketing (? = 0.405) significantly influence brand awareness, with an explanatory power of R² = 0.766 the proposed strategies include enhancing educational and visual content on Instagram, collaborating with relevant micro-influencers, optimizing marketplace listings, and initiating a digital loyalty program, all of these findings highlight the importance of integrating influencer and content marketing strategies to sustainably increase SHAKTI’s digital brand visibility.